2022
DOI: 10.3389/fgene.2022.982241
|View full text |Cite
|
Sign up to set email alerts
|

The expression and methylation of PITX genes is associated with the prognosis of head and neck squamous cell carcinoma

Abstract: Background: The PITX gene family, comprising PITX1, PITX2, and PITX3, is critical in organogenesis and has been evolutionary conserved in animals. PITX genes are associated with the advanced progression and poor prognosis of multiple cancers. However, the relationship between the PITX genes and head and neck squamous cell carcinoma (HNSC) has not been reported.Methods: We used data from The Cancer Genome Atlas (TCGA) to analyze the association between PITX mRNA expression and clinicopathological parameters of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
1
0
Order By: Relevance
“…The heatmap displayed the distribution of clinical data for two different expression groups of TRIB3. Furthermore, TRIB3 expression was significantly correlated with the T-stage, and patients with higher T-stage had significantly higher TRIB3 expression than lower T-stage patients ( Figure 4E ), which suggests that TRIB3 expression is related to tumor growth and infiltration ability ( 33 ).…”
Section: Resultsmentioning
confidence: 97%
“…The heatmap displayed the distribution of clinical data for two different expression groups of TRIB3. Furthermore, TRIB3 expression was significantly correlated with the T-stage, and patients with higher T-stage had significantly higher TRIB3 expression than lower T-stage patients ( Figure 4E ), which suggests that TRIB3 expression is related to tumor growth and infiltration ability ( 33 ).…”
Section: Resultsmentioning
confidence: 97%
“…This reduction might be linked to PITX1 hypermethylation. Additionally, patients with elevated PITX1 expression experienced worse stage, grade, and relapse-free survival (RFS) which was an opposing result of Takenobu et al The databases also suggested correlations between PITX1 and immune cell expression, including CD4+ and CD8+ T cells (25,40). However, relying solely on public databases might limit the accuracy of these predictions.…”
Section: Head and Neck Squamous Cell Carcinomamentioning
confidence: 99%